Ferroptosis as a New Type of Cell Death and its Role in Cancer Treatment - Skoupilová, Hana; Michalová, Eva; Hrstka, Roman (Klinicka onkologie, 2018)
BACKGROUND: Ferroptosis is a recently discovered type of cell death. It is genetically, morphologically, and biochemically distinct from other types of programmed cell death, such as necrosis, apoptosis, and autophagy. The level of intracellular free iron and reactive oxygen species formation are important for ferroptosis activation, which can occur through either of two key inhibitory processes. The first one involves inhibition of cystine transfer into cells by the cystine/glutamate antiporter system (Xc-). Cystine serves as a precursor for the synthesis of glutathione, a major cellular antioxidant. The second one involves the inhibition of glutathione peroxidase 4, which protects cells from lipid peroxidation. Ferroptosis is associated with many metabolic disorders, including neurological diseases and cancer. Molecules involved in the activation of ferroptotic pathways are involved in protecting cells against stress conditions, and in the maintenance of nicotinamide adenine dinucleotide phosphate and glutathione levels, as well as iron homeostasis. Also important is the connection with autophagy, so called ferritinophagy, in which iron is released from lysosomes into the cytosol. Cascade reactions of free unstable iron atoms with other molecules result in the production of reactive oxygen species that initiate the cellular stress that triggers ferroptosis. In diseases such as cancer where cell death inducing mechanisms, including apoptosis, are usually suppressed by genetic changes, the induction of alternative pathways leading to cell death could provide an attractive treatment strategy. CONCLUSION: In recent years, research into new antimetastatic drugs has focused on the activation of alternative cell death pathways that might overcome disturbed metabolic processes inside cancer cells or the chemotherapy resistance acquired in the course of routine treatment. A number of molecules have been found to induce ferroptosis in tumor cells, suggesting that they may offer new alternatives for anticancer treatment. Key words: cell death - cancer - autophagy - ferroptosis - ferritinophagy - cellular stress - ROS This work was supported by the projects GAČR 17-05838S, MEYS - NPS I - LO1413 and MH CZ- -DRO (MMCI, 00209805). The authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers. Accepted: 31. 8. 2018.
Keywords: železo; nádory; cell death - cancer - autophagy - ferroptosis - ferritinophagy - cellular stress - ROS This work was supported by the projects GAČ R 17-05838S; reaktivní formy kyslíku; MEYS - NPS I - LO1413 and MH CZ- -DRO (MMCI; buněčná smrt; or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers. Accepted: 31. 8. 2018; products; Humans; Iron; Reactive Oxygen Species; lidé; Cell Death; 00209805). The authors declare they have no potential conflicts of interest concerning drugs; Neoplasms